Modeling and engine performance of direct injection Hydrogen fueled engine - Md.Mustafizur, Rahman; Mohammed K., Mohammed; Rosli, A. Bakar; Muhamad, Mat Noor; Kumaran, Kadirgama (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.